How Efficient Is Fertilization by Traumatic Insemination in Orius insidiosus (Hemiptera: Anthocoridae)? - Ajila, Henry E. Vacacela; Michaud, J. P.; Abdelwahab, Ahmed H.; Kuchta, Sara [UNESP]; Stowe, Hannah E. (Oxford Univ Press Inc, 2019)
Traumatic insemination (TI) can be injurious to females, and females have evolved various paragenital structures to mitigate these impacts. We examined the mating behavior of Orius insidiosus (Say) and the consequences of single and double matings for female fitness. A total of 100 virgin females (4-6-d old) were directly observed while they mated with virgin males. Some of these females were mated a second time with a different, nonvirgin male 3-5 d later, after they oviposited in sunflower stems. Females were held in isolation, fed eggs of Ephestia kuehniella Zeller, and reproductive success was tracked for 30 d. Six females died during their first copulation (6%), and another within 48 h, without laying eggs. Four percent of the females died during their second copulations. Copulations lasting less than 90 s usually did not result in successful fertilization, and duration of copula was positively correlated with egg fertility in singly-mated females. Duration of copula was more than halved in second matings, twice as variable, and negatively correlated with 30 d fecundity. Thirty-seven percent of singly-mated females and 31% of twice-mated females were infertile, with fewer than half of all females producing 88% of all eggs. We conclude that O. insidiosus females are likely monandrous in the wild, and that TI in this species is inefficient, contributing to high variation in female fitness. Thus, mating involves a significant mortality risk for females, despite their possession of complex paragenital structures that ostensibly mitigate copulatory injury.
Keywords: fertility; mating cost; monandry; polyandry; sexual conflict